Finance and Development, June 2017. (Finance and Development; Finance and Development ;, 2017)
This paper focuses on millennials who are increasingly looking to find their way in the sharing economy, a phenomenon made possible by the emergence of digital platforms that facilitate the matching of buyer and seller. Jobs in the sharing economy-like driving for Uber or Lyft-help some millennials make ends meet, even if such temporary gigs are a far cry from the fulltime jobs with traditional pension plans and other benefits their parents often enjoyed. This generation also enthusiastically embraces the services of the sharing economy, which provides access to everything from beds to cars to boats without the hassle of ownership. Loath to buy big-ticket items such as cars and houses, millennials have sharply different spending habits from those of preceding generations. Millennials confront obstacles to prosperity that their parents didn't face. They are better educated than previous generations-but in today's world, that is not enough to guarantee financial success.